Inklusivitas dan Aksesibilitas Desain Wayfinding Pada Transportasi Publik Jak Lingko - Azura, Jeihan; Mansoor, Alvanov Zpalanzani; Masnoor, Alvanov Zpalanzani (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
Jakarta's public transportation system plays an important role in supporting urban mobility. The Jak Lingko program integrates TransJakarta, MRT, LRT, and KRL modes into one system. This study examines the extent to which the Jak Lingko Wayfinding system is inclusive and accessible to various user groups. The methods used are literature study and field observation as users, with a Wayfinding theory approach from Calori & Vanden-Eynden (2015) and universal design principles based on the BART Facility Standards in the Jakarta Public Transportation Iconography and Wayfinding Guidebook (ITDP Indonesia & FDTJ, 2021). The results of the study show that there are still obstacles to inclusivity at bus stops built before 2020 due to the absence of integrated navigation standards from the government. This study emphasizes the importance of implementing universal design principles comprehensively so that the transportation system can be accessed and used independently by all groups. These findings are expected to be the basis for developing a more participatory and user-oriented Wayfinding system.